P53-Induced inflammation exacerbates cardiac dysfunction during pressure overload. (August 2015) - Yoshida, Yohko; Shimizu, Ippei; Katsuumi, Goro; Jiao, Shuang; Suda, Masayoshi; Hayashi, Yuka; Minamino, Tohru
Abstract: The rates of death and disability caused by severe heart failure are still unacceptably high. There is evidence that the sterile inflammatory response has a critical role in the progression of cardiac remodeling in the failing heart. The p53 signaling pathway has been implicated in heart failure, but the pathological link between p53 and inflammation in the failing heart is largely unknown. Here we demonstrate a critical role of p53-induced inflammation in heart failure. Expression of p53 was increased in cardiac endothelial cells and bone marrow cells in response to pressure overload, leading to up-regulation of intercellular adhesion molecule-1 (ICAM1) expression by endothelial cells and integrin expression by bone marrow cells. Deletion of p53 from endothelial cells or bone marrow cells significantly reduced ICAM1 or integrin expression, respectively, as well as decreasing cardiac inflammation and ameliorating systolic dysfunction during pressure overload. Conversely, overexpression of p53 in bone marrow cells led to an increase of integrin expression and cardiac inflammation that reduced systolic function. Norepinephrine markedly increased p53 expression in endothelial cells and macrophages. Reducing β2 -adrenergic receptor expression in endothelial cells or bone marrow cells attenuated cardiac inflammation and improved systolic dysfunction during pressure overload. These results suggest that activation of the sympathetic nervous system promotes cardiac inflammation by up-regulating ICAM1 and integrin expression via p53 signaling to exacerbate cardiac dysfunction. Inhibition of p53-induced inflammation may be a novel therapeutic strategy for heart failure. Highlights: Expression of p53 is up-regulated in cardiac endothelial cells after TAC. Expression of p53 is up-regulated in bone marrow cells after TAC. Deletion of p53 from these cells attenuates cardiac inflammation. Activation of the sympathetic nervous system up-regulates p53 expression. The interaction between ICAM-1 and integrins is crucial for cardiac inflammation.